Handheld Wi-Fi applications in ambulance systems - Chen, Bin (University of Ottawa (Canada), 2007)
This thesis describes the design and implementation of handheld Wi-Fi applications in ambulance systems, which propose a solution that allows ambulance staff to access remote resources in Emergent Medical Services (EMS) from any location, record life measurements on site by using handheld PCs, and transfer patients' life measurements to the Emergency Room (ER) on the way to the hospital. The handheld Wi-Fi applications aim to provide mobility and efficiency for ambulance staff when saving a life. The handheld Wi-Fi applications afford ambulance staff more flexibility and high performance in accessing and sharing the patient's life data between the ambulance centre and hospitals in time-sensitive circumstances. The handheld Wi-Fi applications provide instant information transportation support for both ambulance staff and healthcare staff. The patient's life measurements are received before the ambulance reaches the hospital.
Keywords: Engineering, System Science.